Male Field Hockey Players’ Academic Performance: How Diet, Financial Support, and Management Play a Role - Ali, Asif; Azam, Muhammad; Rasheed, Abdul (Annals of Human and Social Sciences, 2022)
Much past research on varsity student-athletes mainly emphasized assessing the factors associated with athletic success and performance. Enhancement of academic performance is also an equally important issue in student-athletes’ lives that the researchers have ignored to date. This research aimed to examine how factors like management, financial support, and diet affect the academic performance of university student-athletes. The participants were 126 field hockey players from eleven universities. We used a five-point Likert scale questionnaire to gather information for this cross-sectional study. That comprised twenty-four items related to four constructs: management, financial support, diet, and academic performance. The data collection tool exhibited adequate reliability (Cronbach’s alpha, .767). We analyzed data using chi-square and simple linear regression tests, and the results indicated that management, diet, and financial support were significantly associated with varsity athletes’ academic success. The findings suggest that effective management, sufficient financial assistance, and a healthy diet may contribute to the academic success of university athletes. This study is unique because earlier research mostly neglected student-athletes academics and concentrated on their athletic achievement. At the same time, academic and sports management are essential factors that need to be examined regarding student-athletes’ academic progress. The study results have important implications for policymakers and professionals related to higher education, academic performance, sports management, and parents. Further studies are recommended to assess the generalizability of this data’s findings